Citation analysis of information studies students' dissertations and its application to collection development. - Lee, Vernon Tsu Tsuan. (2008)
Studying the use of journals by students is a method that academic libraries can employ to evaluate its journal collection.In this study, the bibliographies in the dissertations of MSc (Information studies) students at the Nanyang Technological University (NTU) are analyseed, with the objective of evaluating the use of the journal collection in the NTU library by these students. Journal selection and cancellation may be done on the basis of use, in terms of the number of times a journal is cited and the number of students citing the journal, to maximize the usefulness of the journals purchased using the library gadget. The subject categories of journals as well as the publication dates of articles cited are also analysed to evaluate the completeness of the current journal collection used by these postgraduate students.